Globalization and the car industry in China - Donnelly, Tom (Henry Stewart Talks, 2013)
The Chinese state, Theories of Foreign Direct Investment (FDI), Joint ventures, The Chinese automotive industry to 1978, The Open Door Policy, Motives of multinational enterprises (MNEs), JVs and the Chinese government, The growth phase from 1990 -Sources of growth, The current state of the Chinese automotive industry -Weaknesses in the Chinese automotive industry, Government policy responses to weaknesses, Conclusion